Prediction of Body Image Dissatisfaction Based on Spiritual Intelligence and Socio-cultural Patterns in Women Attending Gyms in Yazd - Fahimeh Dehghani; Mahboubeh Atarnia; Seyed Kazem Alavi Langroudi (Hamadan University of Medical Sciences, 2018)
Background and Objective: Body image is a multifactorial concept, which is one of the most fundamental concerns for individuals. We aimed to predict body image dissatisfaction based on spiritual intelligence and socio-cultural patterns in women attending gyms in Yazd, Iran. Materials and Methods: This descriptive correlational study was performed among female residents of Yazd who participated sports classes in 2015. Overall, 351 individuals were selected by using the random cluster sampling method. The data collection instruments included Body Image Concern Inventory, as well as spiritual intelligence and socio-cultural patterns questionnaires. To analyze the data, Pearson correlation coefficient and multivariate regression analysis tests were run in SPSS, version 22. Results: We found a negative correlation between spiritual intelligence and body image dissatisfaction. Moreover, there was a significant positive correlation between socio-cultural patterns and body image dissatisfaction (P≤0.05). In addition, both spiritual intelligence and socio -cultural patterns predicted body image dissatisfaction, yet spiritual intelligence was a stronger contributing factor. Conclusion: Results showed that spiritual intelligence and socio-cultural patterns play a significant role in the anticipation of body image dissatisfaction. However, the former is a stronger predictor of body image dissatisfaction as compared to the latter. Therefore, a survey of effectiveness of spiritual intelligence training sessions to reduce body image dissatisfaction is suggested for future research.